2016
DOI: 10.1093/ndt/gfw352
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic associates of atrial fibrillation in end-stage renal disease

Abstract: ESRD patients with AF show more advanced changes in the LA substrate than ESRD patients without AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…AF atrial fibrillation remodeling [8]. In addition, various studies have demonstrated the prognostic impact of PA-TDI duration on the occurrence of new-onset AF, postoperative AF and AF recurrence after cardioversion or ablation, thereby implicitly strengthening its validity [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Validation and Determinants Of Pa-tdi Durationmentioning
confidence: 99%
“…AF atrial fibrillation remodeling [8]. In addition, various studies have demonstrated the prognostic impact of PA-TDI duration on the occurrence of new-onset AF, postoperative AF and AF recurrence after cardioversion or ablation, thereby implicitly strengthening its validity [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Validation and Determinants Of Pa-tdi Durationmentioning
confidence: 99%
“…Так, по данным B. Franczyk и соавт., объем левого предсердия и масса миокарда левого желудочка не связаны с риском развития ФП у больных, находящихся на диализе, в отличие от пациентов в общей популяции [13]. В работе L. C. Hensen и соавт., напротив, было продемонстрировано, что индексированный объем левого предсердия, показатель А, отражающий максимальную скорость позднего наполнения левого желудочка, как при оценке трансмитрального кровотока, так и при тканевой допплерометрии, были независимо связаны с риском развития ФП у диализных больных [14].…”
unclassified
“…18,19 In a study by Voroneanu et al when the echocardiographic findings of patients with AF were examined, it was observed that the left atrium diameters increased and the ejection fractions were lower. 20,21 In our study, it was determined that as the dialysis time increased, the frequency of AF also increased; however, there was no significant relationship in terms of left atrium diameter and left ventricular functions. To evaluate the reasons for this, our patient Epicardial fat tissue is the visceral fat tissue of the heart.…”
Section: Discussionmentioning
confidence: 54%
“…It was reported that other ECO findings and dialysis type had no relationship with AF development 18,19 . In a study by Voroneanu et al when the echocardiographic findings of patients with AF were examined, it was observed that the left atrium diameters increased and the ejection fractions were lower 20,21 …”
Section: Discussionmentioning
confidence: 99%